Subsidence surveys at Olkaria geothermal field, Kenya. Issue 1 (2nd January 2017) - Koros, Wesley Kipngenoh; Agustin, Fitriani
Abstract: Subsidence is conventionally measured by comparing levels on benchmarks that are derived by survey levelling techniques from surveys carried out some epochs apart. Subsidence is usually expressed as an annual rate. The Olkaria geothermal field in Kenya has an extensive benchmark network established in 1983 that has not been levelled since. The field operator is tasked with accelerating generation of electricity from geothermal resources to meet the demands of the population. This may lead to environmental challenges like subsidence. The advent of digital levels and use of traditional precise levelling techniques can achieve high accuracies over short distances. The InSAR technique has been applied in the geothermal field to observe subsidence despite shorter periods of image acquisition. Subsidence levelling data can also be used for gravity surveys and for the design and setting out of geothermal engineering projects. Similar survey techniques have been used worldwide to monitor subsidence in geothermal areas.